2022
DOI: 10.1007/s00170-022-08878-x
|View full text |Cite
|
Sign up to set email alerts
|

High virucidal potential of novel ceramic–metal composites fabricated via hybrid selective laser melting and spark plasma sintering routes

Abstract: In this work, we combine selective laser melting (SLM) and spark plasma sintering (SPS) to fabricate new materials with high virucidal potential. Various bioactive disc-shaped ceramics, metal alloys, and composites were fabricated and tested against bacteriophage Phi6-a model system for RNA-enveloped viruses. We prepared silver-doped titanium dioxide (TiO 2 + 2.5-10% Ag), copper-doped titanium dioxide (TiO 2 + 2.5-10% Cu), Cu2NiSiCr, and Cu15Ni8Sn composite materials (metal lattices filled with ceramics). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…By doing so, it becomes feasible to fabricate complex architectures with dense microstructures and achieve continuous plastic deformation at a higher strain rate [157]. Beyond its mechanical, electrical, and thermal properties, pure or alloyed copper in lattice or bulk structures exhibits antiviral and self-cleaning effects [158]. Notably, Cu-based alloys combined with Ag and TiO 2 create a novel highly virucidal cermet composite [115].…”
Section: In Vivo In Vitro and In Silico Studiesmentioning
confidence: 99%
“…By doing so, it becomes feasible to fabricate complex architectures with dense microstructures and achieve continuous plastic deformation at a higher strain rate [157]. Beyond its mechanical, electrical, and thermal properties, pure or alloyed copper in lattice or bulk structures exhibits antiviral and self-cleaning effects [158]. Notably, Cu-based alloys combined with Ag and TiO 2 create a novel highly virucidal cermet composite [115].…”
Section: In Vivo In Vitro and In Silico Studiesmentioning
confidence: 99%
“…For instance, during the COVID-19 pandemic, PBF-PM integration was employed to produce an antiviral metal-ceramic (cermet) composite that demonstrated strong virucidal capabilities for in vitro use. As a result, combining various methods using a hybrid approach can result in hybrid composites comprising a blend of materials [43,44]. Environmental sustainability is one of the most important factors in the Industry 5.0 revolution; it is closely related to additive manufacturing, and it is depicted in Figure 4.…”
Section: Industry 50: Hct Am and Esmentioning
confidence: 99%
“…For instance, during the COVID-19 pandemic, PBF-PM integration was employed to produce an antiviral metal-ceramic (cermet) composite that demonstrated strong virucidal capabilities for in vitro use. As a result, combining various methods using a hybrid approach can result in hybrid composites comprising a blend of materials [43,44].…”
Section: Industry 50: Hct Am and Esmentioning
confidence: 99%
“…Along with this, in recent studies, scientists have demonstrated the possibility of using the SPS technique to obtain ceramic composites reinforced with cellular titanium alloy matrices (Ti6Al4V, known for medical applications [27][28][29][30]) manufactured by additive 3D printing technologies. Only three studies, all of which were performed by Rahmani et al, are known in this area [31][32][33], where the method of combining the selective laser melting technology and SPS was applied to obtain the following medical biocomposites: Ti6Al4V-TiO 2 /Ag and Ti6Al4V-CaSiO 3 . Antibacterial properties of these biocomposites, as well as their high mechanical characteristics, have been demonstrated and substantiated in detail in these studies.…”
Section: Introductionmentioning
confidence: 99%